Medium and low temperature preparation method of refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement and cement product

By adding desulfurization gypsum to cement clinker and combining refined steel slag, titanium gypsum, calcium carbide slag and bauxite, the directional ore phase composition is designed, which solves the problem that refined steel slag and titanium gypsum is difficult to directly apply to cement production, and achieves the The medium and low temperature preparation of low-carbon sulfur aluminate cement has improved the strength and utilization rate of cement and promoted environmental protection and sustainable development.

CN119461910APending Publication Date: 2025-02-18GUILIN UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411737946.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The iron oxide content of refined steel slag is extremely low and cannot be directly used as a firing raw material for cement clinker containing iron phase. Moreover, due to low grade, high viscosity, color and other problems, it is difficult to deal with and low utilization rate, resulting in large accumulation of titanium gypsum. Environmental pollution.

Method used

The clinker fired at medium and low temperature is mixed with 5~10%wt of desulfurization gypsum, combined with refined steel slag, titanium gypsum, calcium carbide slag and bauxite, and a directional precision ore phase is designed to form calcium sulfa aluminate and dicalcium silicate. , minerals such as tetracalcium sulfate and calcium titanate stimulate the gelling activity of γ-type dicalcium silicate and improve the strength of cement.

Benefits of technology

The simultaneous utilization of refined steel slag and titanium gypsum has been achieved, which reduces the calcination temperature of cement clinker, saves energy consumption, reduces carbon emissions, improves the mechanical properties and utilization of cement, promotes efficient treatment of solid waste resources and environmental protection and sustainable development. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461910A_ABST
    Figure CN119461910A_ABST
Patent Text Reader

Abstract

The invention discloses a medium and low temperature preparation method of refined steel slag-titanium gypsum based low-carbon sulphoaluminate cement and a cement product. The method comprises the following steps: S1, drying and grinding: drying, grinding and sieving four raw materials, namely refined steel slag, titanium gypsum, carbide slag and bauxite, and storing in parts by weight for later use; s2, proportioning and homogenizing: mixing and homogenizing 13-20 parts of refined steel slag, 20-28 parts of titanium gypsum, 30-40 parts of carbide slag and 25-32 parts of bauxite by using a mixer; s3, calcining the raw material: tabletting the raw material, calcining at 1250-1300 DEG C, and keeping the temperature for 30-60 minutes to obtain cement clinker; s4, grinding the clinker: grinding and sieving (0.075 mm); and S5, doping desulfurized gypsum: doping 5-10% wt of desulfurized gypsum into 95-90% wt of cement clinker, and uniformly mixing to obtain a cement finished product. Two industrial solid wastes of the refined steel slag and the titanium gypsum can be used at the same time, calcium and siliceous substances in the refined steel slag and sulfur (dihydrate gypsum) and iron substances in the titanium gypsum are fully utilized, utilization of solid waste resources is achieved, and meanwhile emission of carbon dioxide is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of building materials and solid waste utilization, and in particular relates to a solid waste-based low-carbon sulphoaluminate cement production technology, and specifically relates to a medium- and low-temperature preparation method of refined steel slag-titanium gypsum low-carbon sulphoaluminate cement and a cement product. Background Art

[0002] Refined steel slag is a by-product produced in the steelmaking process. It is a solid waste and is grayish white. After the refined steel slag is treated with iron recovery, the iron oxide content is extremely low and it cannot be directly used as a raw material for iron-containing cement for raw material batching. The invention patent (application number CN201910300484.4, publication number CN109987866A, publication date July 9, 2019) discloses a method and system for producing low-alkalinity, new mineral system sulphoaluminate cement using steel slag. The method includes the following steps: mixing and homogenizing the ground steel slag with dried desulfurized gypsum, aluminum ash and carbide slag according to a set ratio; transporting the homogenized raw material to a rotary kiln for calcination at a calcination temperature of 1200-1270 ° C and a calcination time of 20-60 min to obtain cement clinker; the alkalinity coefficient of the homogenized cement raw material is 0.81-0.9, and the content of Fe2O3 is 8-13%. In this patent application, the steel slag used has a relatively high iron oxide content and can be directly used as a raw material for sulphoaluminate cement for raw material batching. However, the refined steel slag used in this patent cannot be directly used as a raw material in this patent because its iron content is extremely low. The activity of refined steel slag is also much lower than that of general steel slag. General steel slag contains a certain amount of β-type dicalcium silicate (β-C2S), which helps to exert a certain degree of gelling property and is beneficial to the development of cement strength. However, refined steel slag is mainly γ-type dicalcium silicate (γ-C2S), which has weak gelling property, so it is difficult to be directly applied to cement as a cement admixture. Refined steel slag contains a large amount of CaO and SiO2, which can be indirectly used as a raw material for burning cement clinker. During the high-temperature calcination process, γ-type dicalcium silicate can be converted into other crystal forms (such as β-type and α′-type) to enhance its gelling property. The refined steel slag of general steel mills is fine powder, and some of them can be used without grinding, and the treatment method before use is simple. At present, the accumulation of refined steel slag will occupy arable land, the cost-effectiveness of expanding slag yards is not high, and there are few places where refined steel slag can be applied, and the utilization rate is not high. If refined steel slag can be used to calcine cement, it can open up new application areas for it.

[0003] Titanium gypsum is an industrial gypsum produced as a byproduct of neutralizing acidic salt wastewater when producing titanium dioxide using the sulfuric acid method. Due to its low grade, high viscosity, color and other issues, it is more difficult to handle than other byproduct gypsums, so it is rarely used in various fields. The large accumulation of titanium gypsum will cause environmental hazards such as air and water pollution. However, the dihydrate gypsum (CaSO4·2H2O) it contains can provide calcium and sulfur components, and the Fe2O3 it contains can complement refined steel slag to supplement the missing iron components in the raw materials. Both can be used in the firing of sulphoaluminate cement clinker.

[0004] Traditional sulphoaluminate cement is made of limestone, bauxite and gypsum. After the raw materials are evenly ground, they are calcined at 1300-1350 ℃. The calcined clinker and a certain amount of gypsum are ground to obtain sulphoaluminate cement. The main clinker minerals are calcium sulphoaluminate, dicalcium silicate and iron phase. It belongs to the CaO-Al2O3-SiO2-SO3- Fe2O3 system. Calcium sulphoaluminate can account for 55-75%wt in the clinker, dicalcium silicate is generally 15-30%wt, and the iron phase accounts for the least, generally 3-6%wt. Sulphoaluminate cement has the characteristics of high early strength, rapid solidification, corrosion resistance, impermeability and frost resistance.

[0005] The invention patent (application number CN201910785706.6, publication number CN110372233A, publication date October 25, 2019) discloses a method for preparing sulphoaluminate cement clinker with the resource utilization of titanium gypsum, and the specific steps are: mixing aluminum ash with titanium gypsum, coal gangue, and carbide slag, grinding the mixed materials to obtain raw materials; injecting the raw materials into a homogenizing tank, mixing them, filtering them, drying them, and calcining them to obtain sulphoaluminate cement clinker. The raw materials contain the following weight ratios: 25-32 parts of titanium gypsum, 7-12 parts of coal gangue, 20-29 parts of aluminum ash, and 25-36 parts of carbide slag. The main problems with this patent are: the aluminum ash used as raw material in this patent needs to be washed and dried, and the raw materials need to be wet-milled, filtered and dried. The process is complicated, the cost is high, more energy is consumed, and more CO2 is emitted. In addition, the main minerals of the clinker in this patent are calcium sulfoaluminate, dicalcium silicate and calcium sulfate.

[0006] In summary, the technical problems existing in the prior art are: the iron oxide content of refined steel slag is extremely low and cannot be directly used as a raw material for the calcination of iron-containing cement clinker. Titanium gypsum is more difficult to handle than other by-product gypsums due to its low grade, high viscosity, color and other problems, so it is rarely used in various fields. The large accumulation of titanium gypsum will cause environmental hazards such as air and water pollution.

[0007] The main technical obstacles to solving the existing technology are that there are many impurities in the solid waste and the mineral composition in the clinker is difficult to control. Since the calcium and aluminum components in refined steel slag and titanium gypsum are insufficient to form the required minerals, auxiliary materials such as carbide slag and bauxite are introduced. The important significance of solving the problems of the existing technology is to simultaneously utilize refined steel slag and titanium gypsum industrial waste to improve the treatment efficiency of solid waste resources, contribute to better environmental protection and sustainable development, reduce production costs, provide technical support for the online preparation of refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement clinker from refined steel slag, improve economic benefits, and promote the development of science and technology.

[0008] Technical Solution Aiming at the technical problems existing in the above-mentioned prior art, the technical purpose of the present invention is to disclose a medium-low temperature preparation method of refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement and a cement product. The method is to add 5-10%wt (this ratio is the mass ratio of desulfurized gypsum to cement) of desulfurized gypsum to the clinker sintered at medium and low temperature, and mix them together to obtain refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement.

[0009] The present invention achieves the technical purpose through the following technical means.

[0010] The overall idea of ​​the method of the present invention is that the γ-type dicalcium silicate in refined steel slag can be converted into other crystal forms (such as β-type and α′-type) at high temperature, and the β-type and α′-type dicalcium silicate are retained by rapid cooling to stimulate their gelling activity. At the same time, the calcium and silicon effective components in the refined steel slag and the sulfur and iron effective components in the titanium gypsum are complementary, and the calcium components in the carbide slag and the aluminum components in the bauxite are also utilized. Through the directional and precise mineral phase composition design, the synergistic effect of these four raw materials is achieved, and the refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement clinker is directional fired at medium and low temperatures. Through the directional and precise mineral phase design, the free magnesium oxide and iron components introduced into the solid waste are chemically combined at high temperature to form ferromagnesian spinel, which achieves the effect of solidifying free magnesium oxide and ensures the stability of cement. The fired cement clinker is mixed with a certain amount of desulfurized gypsum to prepare refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement.

[0011] The technical solution of the present invention is a medium-low temperature preparation method of refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement and a cement product, comprising the following steps: S1. Drying and grinding: The four raw materials are refined steel slag, titanium gypsum, carbide slag and bauxite, which are dried to constant weight at a drying temperature of 105-110°C, ground and sieved, and the size of the sieved powder particles ranges from 0.0005 to 0.075 mm (millimeter). Then, they are mixed according to weight ratio and stored for later use; S2, batching and homogenization: The four raw materials in step S1 are batched by weight, wherein the amount of refined steel slag is 13-20 parts, the amount of titanium gypsum is 20-28 parts, the amount of calcium carbide slag is 30-40 parts, and the amount of bauxite is 25-32 parts. Mix them in a mixer to obtain raw materials. The content of each element in the raw materials is directly obtained by mixing the four raw materials. No additional ingredients need to be added. The content of each element is guaranteed by adjusting the range of three rate values ​​(basicity coefficient, sulfur-aluminum ratio, aluminum-silicon ratio). Among them, in the raw materials, CaO accounts for 35~45wt%, Al2O3 accounts for 20~26wt%, SiO2 accounts for 8~15wt%, SO3 accounts for 5~15wt%, Fe2O3 accounts for 3~10wt%, and the MgO content is less than 1%; the MgO content is preferably 0.5~0.75wt%; wherein wt% is the weight content percentage

[0012] S3, raw material calcination: the raw material tablets have a diameter of 48-52 mm and a height of 5.5-6.5 mm, preferably a round tablet with a diameter of 50 mm and a height of 6 mm. After the raw material tablets are pressed, they are calcined at 1250-1300°C for 30-60 min (minutes) to obtain cement clinker; S4, clinker grinding: After the insulation is completed, the cement clinker is quenched by a blower and quickly cooled to room temperature. The clinker is gray, loose and porous, and easy to grind. The clinker is ground and sieved with a 0.075 mm screen; S5. Adding desulfurized gypsum: Add desulfurized gypsum (5-10%wt) sieved 0.075 mm to the above-mentioned sieved cement clinker (95-90%wt), mix well and obtain the finished cement product. The added desulfurized gypsum is dried at 40-45 ℃. Desulfurized gypsum is a by-product produced in the process of flue gas desulfurization from coal or oil. Its main component is CaSO4·2H2O, which contains some impurities and is a solid waste. The CaSO4·2H2O in the desulfurized gypsum can extend the setting time of cement on the one hand, and on the other hand, during the hydration process of cement, CaSO4·2H2O can react with minerals such as calcium sulfoaluminate to form hydration product calcium sulfonate, thereby improving the mechanical properties of cement.

[0013] Preferably, in step S1, the amount of refined steel slag is 13 parts, the amount of titanium gypsum is 21 parts, the amount of carbide slag is 35 parts, and the amount of bauxite is 31 parts.

[0014] Preferably, in the step S3, the raw material tablets are placed at 1250 ° C for calcination, and the insulation time is 30-60 min to obtain cement clinker. The main mineral phases of the cement clinker are calcium sulfoaluminate, dicalcium silicate, tetracalcium aluminoferrate and calcium titanate. The cement clinker is tested and the proportions are calcium sulfoaluminate (65-72%), dicalcium silicate (18-25%), tetracalcium aluminoferrate (2-5%), and calcium titanate (3-7%).

[0015] Preferably, in step S3, the raw material tablets are calcined at 1275°C for 30-60 min to obtain cement clinker; the main mineral phases of cement clinker are calcium sulfoaluminate, dicalcium silicate, tetracalcium aluminoferrate and calcium titanate. The proportions of cement clinker are calcium sulfoaluminate (65-75%), dicalcium silicate (15-20%), tetracalcium ferrous sulfate (2-5%), calcium titanate (3-7%).

[0016] Preferably, in the step S3, the raw material tablets are calcined at 1300°C for 30-60 min to obtain cement clinker, the main mineral phases of the cement clinker are calcium sulfoaluminate, dicalcium silicate, tetracalcium aluminoferrate and calcium titanate. The cement clinker is tested and the proportions are calcium sulfoaluminate (65-70%), dicalcium silicate (20-25%), tetracalcium aluminoferrate (2-5%), and calcium titanate (3-7%), respectively.

[0017] Preferably, in the step S5, desulfurized gypsum (5%wt) is added to the sieved cement clinker (95%wt), and the mixture is mixed together to obtain a finished cement product.

[0018] Preferably, in the step S5, desulfurized gypsum (10%wt) is added to the sieved cement clinker (90%wt), and the mixture is mixed together to obtain a finished cement product.

[0019] A refined steel slag-titanium gypsum based low carbon sulphoaluminate cement, characterized in that the finished cement product is prepared according to the medium- and low-temperature preparation method of the refined steel slag-titanium gypsum based low carbon sulphoaluminate cement.

[0020] Compared with the prior art, the refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement and the medium- and low-temperature preparation method thereof of the present invention have the following beneficial effects.

[0021] 1. The present invention can use two industrial solid wastes, namely refined steel slag and titanium gypsum, at the same time, making full use of calcium and silicon in refined steel slag, sulfur (dihydrate gypsum) and iron in titanium gypsum, and promoting the utilization of solid waste resources. These two solid wastes contain a small amount of alkali metal compounds, which also helps to reduce the clinker calcination temperature.

[0022] 2. During the clinker calcination process, all effective components participate in the solid phase reaction, mainly generating calcium sulfoaluminate, dicalcium silicate, tetracalcium iron sulfate and calcium titanate, and no free calcium oxide is detected, which will not affect the mineral composition, and free magnesium oxide will be solidified in magnesia-iron spinel. The calcination temperature of 1250-1300 ℃ is 50-100 ℃ lower than the traditional calcination temperature, which greatly saves energy consumption. The use of carbide slag instead of limestone as raw material has the effect of reducing carbon emissions and promoting the development of cement clinker production in the direction of low consumption and low emissions.

[0023] 3. When preparing refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement, 5-10% desulfurized gypsum is added to the above clinker, so that solid waste resources can be utilized again. In addition, the desulfurized gypsum only needs simple drying and screening, and the pre-treatment technology is simple and convenient. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a flow chart of the method of the present invention; Figure 2 This is the calcination temperature diagram of the present invention; this is a calcination temperature curve diagram formulated to generate better clinker, which is divided into different heating stages, and also includes a heat preservation stage and a cooling stage.

[0025] Figure 3 1 is an X-ray diffraction spectrum of cement clinker at a calcination temperature of 1300°C and different holding times in an embodiment of the present invention; in the figure, the meaning of each figure mark is: 1 (calcium sulfoaluminate), 2 (dicalcium silicate), 3 (tetracalcium aluminoferrate), 4 (calcium titanate).

[0026] Figure 4 SEM image of cement clinker calcined at 1250°C in an embodiment of the present invention; Figure 5 SEM image of cement clinker calcined at 1275°C in the embodiment of the present invention; Figure 6 SEM image of cement clinker calcined at 1300°C in an embodiment of the present invention; By observing the SEM images of these clinkers, it was found that the mineral growth was good and the calcination temperature of 1250-1300 ℃ was appropriate. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the scope of protection thereof.

[0028] A medium-low temperature preparation method of refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement and a cement product, comprising the following steps: S1. Drying and grinding: The four raw materials are refined steel slag, titanium gypsum, carbide slag and bauxite, which are dried (to constant weight) at a drying temperature of 105-110 °C, ground, and the particle size ranges from 0.0005 to 0.075 mm. After screening, they are stored for standby use according to the weight ratio. In the prior art, refined steel slag is not used to burn cement clinker. Although titanium gypsum is used to burn cement clinker, its utilization rate is generally not high, and most of them are less than 20%. When the raw material is calcined, the calcium component in the refined steel slag can be combined with the sulfur and iron components in the titanium gypsum to form the required minerals calcium sulfoaluminate and tetracalcium ferroaluminate. The siliceous component in the refined steel slag can also participate in the formation of dicalcium silicate. The Fe in the titanium gypsum will participate in the solid phase reaction, replace part of the Al in the calcium sulfoaluminate, and increase the activity of the calcium sulfoaluminate mineral, thereby increasing the strength of cement.

[0029] Unlike the aluminum ash used as raw material in the prior art, which needs to be washed and dried after washing, and the raw materials need to be wet-milled, the raw materials of the present invention only need to be dried, ground, sieved, and mixed before calcination.

[0030] S2, batching and homogenization: the four raw materials in step S1 are mixed by weight, wherein the amount of refined steel slag is 13-20 parts, the amount of titanium gypsum is 20-28 parts, the amount of calcium carbide slag is 30-40 parts, and the amount of bauxite is 25-32 parts; the four raw materials work synergistically, and the common utilization rate of refined steel slag and titanium gypsum exceeds 30%; a mixer is used to mix and homogenize to obtain a raw material, in which CaO accounts for 35-40wt%, Al2O3 accounts for 20-26wt%, SiO2 accounts for 8-15wt%, SO3 accounts for 5-10wt%, Fe2O3 accounts for 3-8wt%, and the MgO content is less than 1%; S3. Raw material calcination: The raw material is pressed into tablets with a diameter of 48-52 mm and a height of 5.5-6.5 mm. Preferably, the raw material is a round tablet with a diameter of 50 mm and a height of 6 mm. After the raw material is pressed, it is calcined at 1250-1300 °C. When the calcination temperature reaches 1325 °C, the calcium sulfoaluminate in the clinker begins to decompose and a molten state appears. The insulation time is 30-60 min to obtain cement clinker.

[0031] The calcination temperature has a direct relationship with the solid-phase reaction and the formation of the liquid phase. If the calcination temperature is too low, the required minerals cannot be formed, and some transition phases will also exist, such as calcium aluminum feldspar. The hydration performance of this transition phase is poor, which will reduce the compressive strength of the cement. When the calcination temperature is too high, the highly active mineral calcium sulfoaluminate will decompose. The inventors found through experiments that the clinker minerals grow well at a calcination temperature of 1250-1300°C. In addition, due to the high TiO2 content in the raw materials, some calcium titanate is also present in the clinker. This calcination temperature is lower than that of traditional sulfoaluminate cement, which reduces the use of fuel during the calcination stage and saves energy and is environmentally friendly.

[0032] In some embodiments, cement clinker is obtained after the blower is cooled (about 20 minutes), and the cooled clinker is gray. The main component of carbide slag raw material is Ca(OH)2, which will decompose into CaO and H2O at nearly 600°C. It may be that some pores are formed inside the clinker after the water evaporates during the calcination process, resulting in loose and porous clinker, which is easier to crush and grind.

[0033] S4. Clinker grinding: After the insulation, the cement clinker is cooled by a blower. When it cools to room temperature, the clinker is gray, loose and porous, and easy to grind. The clinker is also ground and sieved (0.075 mm). The main mineral phase composition and weight proportion of clinker are calcium sulfoaluminate (65~72%), dicalcium silicate (18~25%), tetracalcium aluminoferrite (2~5%), calcium titanate (3~7%), and a small amount of magnesia-ferrocene spinel.

[0034] Step 6. In some embodiments, the main mineral phase composition and weight proportion of the clinker are calcium sulfoaluminate (65-75%), dicalcium silicate (15-20%), tetracalcium aluminoferrite (2-5%), calcium titanate (3-7%), and a small amount of ferromagnesian spinel.

[0035] Step 7. In some embodiments, the main mineral phase composition and weight proportion of the clinker are calcium sulfoaluminate (65-70%), dicalcium silicate (20-25%), tetracalcium aluminoferrite (2-5%), calcium titanate (3-7%), and a small amount of ferromagnesian spinel.

[0036] Through the analysis of clinker, it was found that part of the iron participated in the reaction of forming calcium sulfoaluminate in the solid phase reaction, a small part of Al was replaced by Fe, and the crystal form of the generated calcium sulfoaluminate also changed, which promoted the hydration of cement to a certain extent. This phenomenon also led to a decrease in the amount of iron phase generated.

[0037] S5, adding desulfurized gypsum: adding desulfurized gypsum (5-10%wt) sieved with 0.075 mm to the above-mentioned sieved cement clinker (95-90%wt), and mixing them together to obtain a cement product. The present invention adds desulfurized gypsum, and studies the effect of different desulfurized gypsum dosages on the compressive strength of cement paste.

[0038] The fired cement clinker is mixed with 5-10%wt of desulfurized gypsum (passed through a 0.075 mm square hole sieve), and after mixing and homogenization, refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement is obtained.

[0039] Example 1 The refined steel slag, titanium gypsum and other raw materials are dried in an oven, ground, and sieved for use. The weight ratio is: 13 parts of refined steel slag, 21 parts of titanium gypsum, 35 parts of calcium carbide slag, and 31 parts of bauxite. The raw materials are mixed evenly to obtain raw materials. The raw materials are calcined at a temperature of 1250 ° C in a muffle furnace, and the insulation time is 60 min. The calcination system is as follows: Figure 2 As shown in the figure, in order to produce better clinker, the calcination system is divided into different heating stages, including the heat preservation stage and the cooling stage. The main minerals of clinker are calcium sulfoaluminate, dicalcium silicate, tetracalcium aluminoferrate and calcium titanate. The scanning electron microscope image of clinker (magnification 5000 times) is shown in the figure. Figure 4 As shown, Figure 4 This is a scanning electron microscope image of cement clinker calcined at 1250 °C in an embodiment of the present invention. Angular calcium sulfoaluminate minerals can be observed, with a size generally between 1 and 4 μm, and good mineral growth. In addition, there are gaps between the minerals, which makes the clinker loose, which is conducive to grinding, and also conducive to the contact between the minerals and water, promoting hydration reactions. . The clinker is mixed with 5% desulfurized gypsum to make a finished cement product. The 1-day, 3-day, 7-day and 28-day compressive strengths of the cement paste are 43.4 MPa, 63.4 MPa, 69.9 MPa and 83.1 MPa, respectively.

[0040] Table 1 Main mineral composition weight percentage (wt%) of clinker calcined at 1250℃ Main ingredients Calcium sulphoaluminate Dicalcium Silicate Tetracalcium aluminoferrite Calcium Titanate Quality score 70.3 19.3 3.1 6.6 Example 2 The equipment used in Example 2 is the same as that in Example 1. The raw materials such as refined steel slag and titanium gypsum are dried in an oven, ground, and sieved for use. The proportions are as follows: 13 parts of refined steel slag, 21 parts of titanium gypsum, 35 parts of calcium carbide slag, and 31 parts of bauxite. The raw materials are mixed evenly to obtain raw materials. The raw materials are calcined at a temperature of 1275 ° C and the heat preservation time is 60 min. The calcination temperature is as follows: Figure 2 The main minerals of clinker are calcium sulfoaluminate, dicalcium silicate, tetracalcium aluminoferrate and calcium titanate. The scanning electron microscope image of clinker (magnification 5000 times) is shown in Figure 5shown. Figure 5 This is a scanning electron microscope image of cement clinker calcined at 1275 °C in an embodiment of the present invention. Angular calcium sulfoaluminate minerals and dicalcium silicate minerals can be observed. The mineral size is generally between 1 and 5 μm, and the minerals grow well. In addition, there are many gaps between the minerals, which is beneficial to the clinker powder and the contact between the minerals and water, promoting the hydration reaction. The clinker is mixed with 5% desulfurized gypsum to make a finished cement product. The 1-day, 3-day, 7-day and 28-day compressive strengths of the cement paste are 37.7 MPa, 61.6 MPa, 66.9 MPa and 78.3 MPa, respectively.

[0041] Table 2 Main mineral composition of clinker calcined at 1275 °C (wt%) Main ingredients Calcium sulphoaluminate Dicalcium Silicate Tetracalcium aluminoferrite Calcium Titanate Quality score 72.5 17.8 2.3 6.6 Example 3 The equipment used in Example 3 is the same as that in Example 1. The raw materials such as refined steel slag and titanium gypsum are dried in an oven, ground, and sieved for use. The proportions by weight are: 13 parts of refined steel slag, 21 parts of titanium gypsum, 35 parts of calcium carbide slag, and 31 parts of bauxite. The raw materials are mixed evenly to obtain raw materials. The raw materials are calcined at a temperature of 1300°C, and the holding time is 30 min and 60 min respectively. The calcination temperature is as follows: Figure 2 The X-ray diffraction patterns at different holding times are shown in Figure 3 As shown, Figure 3 1 is an X-ray diffraction spectrum of cement clinker at a calcination temperature of 1300° C. and different holding times in the embodiment of the present invention. The main minerals are calcium sulfoaluminate, dicalcium silicate, calcium titanate and tetracalcium aluminoferrate. Figure 3 It shows that the amount of minerals generated by keeping warm for 60 min is more than that by keeping warm for 30 min (judged by the diffraction intensity), and keeping warm for 60 min is better.

[0042] The main minerals of clinker are calcium sulfoaluminate, dicalcium silicate, tetracalcium aluminoferrate and calcium titanate. The scanning electron microscope image of clinker (magnification 5000 times) is as follows: Figure 6 As shown, Figure 6 This is a scanning electron microscope image of cement clinker calcined at 1300 °C in an embodiment of the present invention. Angular calcium sulfoaluminate minerals can be observed. The mineral size is generally between 1 and 3 μm, and the mineral growth is normal. There are fewer gaps between the minerals, it is difficult for the minerals to contact with water, and the hydration reaction is relatively slow. The clinker is mixed with 5% desulfurized gypsum to make a cement product. The 1-day, 3-day, 7-day and 28-day compressive strengths of the cement paste are 43.0 MPa, 64.6 MPa, 74.4 MPa and 71.7 MPa, respectively.

[0043] Table 3 Main mineral composition of clinker calcined at 1300℃ (wt%) Main ingredients Calcium sulphoaluminate Dicalcium Silicate Tetracalcium aluminoferrite Calcium Titanate Quality score 68.3 22.8 2.4 5.3 Comparative Example 1 10% of desulfurized gypsum was added to the clinker in Example 1 and mixed to form a cement product. The 1-day, 3-day, 7-day and 28-day compressive strengths of the cement paste were 47.3 MPa, 66.0 MPa, 73.9 MPa and 74.5 MPa, respectively.

[0044] Comparative Example 2 The clinker in Example 2 was mixed with 10% desulfurized gypsum and mixed to form a cement product. The 1-day, 3-day, 7-day and 28-day compressive strengths of the cement paste were 41.6 MPa, 63.4 MPa, 70.3 MPa and 71.9 MPa, respectively.

[0045] Comparative Example 3 The clinker in Example 3 was mixed with 10% desulfurized gypsum and mixed to form a cement product. The 1-day, 3-day, 7-day and 28-day compressive strengths of the cement paste were 44.5 MPa, 62.6 MPa, 71.7 MPa and 70.3 MPa, respectively.

[0046] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principles of the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement at medium and low temperatures, comprising the following steps: S1. Drying and grinding: The four raw materials are refined steel slag, titanium gypsum, carbide slag and bauxite, which are dried (to constant weight) at a drying temperature of 105-110 °C, ground and sieved, and the particle size range of the sieved powder is 0.0005-0.075 mm, and then stored according to the weight ratio; S2, batching and homogenization: the four raw materials in step S1 are batched according to weight proportions, wherein: 13-20 parts of refined steel slag, 20-28 parts of titanium gypsum, 30-40 parts of carbide slag and 25-32 parts of bauxite are mixed in a mixer to obtain raw material; S3, raw material calcination: the raw material is pressed into tablets with a diameter of 48-52 mm and a height of 5.5-6.5 mm, preferably a round tablet with a diameter of 50 mm and a height of 6 mm. After the raw material is pressed into tablets, it is calcined at 1250-1300°C for 30-60 min to obtain cement clinker; S4. Clinker grinding: After the insulation, the cement clinker is cooled by a blower. When it cools to room temperature, the clinker is gray, loose and porous, and easy to grind. The clinker is also ground and sieved (0.075 mm). S5. Adding desulfurized gypsum: Add desulfurized gypsum (5-10%wt) sieved with 0.075 mm to the above-mentioned sieved cement clinker (95-90%wt), mix them together to obtain a cement product. The added desulfurized gypsum is dried at 40-45°C.

2. The method for preparing a medium- and low-temperature refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement according to claim 1, characterized in that: In the step S1, the amount of refined steel slag is 13 parts, the amount of titanium gypsum is 21 parts, the amount of calcium carbide slag is 35 parts, and the amount of bauxite is 31 parts.

3. The method for preparing a medium- and low-temperature refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement according to claim 1, characterized in that: In the step S3, the raw material tablets are placed at 1250° C. for calcination, and the heat preservation time is 30-60 min to obtain cement clinker. The main mineral phases of the cement clinker are calcium sulfoaluminate, dicalcium silicate, tetracalcium aluminoferrate and calcium titanate, and the proportions are calcium sulfoaluminate (65-72%), dicalcium silicate (18-25%), tetracalcium aluminoferrate (2-5%), and calcium titanate (3-7%), respectively.

4. The method for preparing a medium- and low-temperature refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement according to claim 1, characterized in that: In step S3, the raw material tablets are calcined at 1275°C for 30-60 minutes to obtain cement clinker; the main mineral phases of the cement clinker are calcium sulfoaluminate, dicalcium silicate, tetracalcium aluminoferrate and calcium titanate. The proportions are respectively calcium sulfoaluminate (65-75%), dicalcium silicate (15-20%), iron phase (2-5%), and calcium titanate (3-7%).

5. The method for preparing a medium- and low-temperature refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement according to claim 1, characterized in that: In the step S3, the raw material tablets are calcined at 1300°C for 30-60 min to obtain cement clinker. The main mineral phases of the cement clinker are calcium sulfoaluminate, dicalcium silicate, tetracalcium aluminoferrate and calcium titanate, and the proportions are calcium sulfoaluminate (65-70%), dicalcium silicate (20-25%), tetracalcium aluminoferrate (2-5%), and calcium titanate (3-7%), respectively.

6. The method for preparing a medium- and low-temperature refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement according to claim 1, characterized in that: In the step S5, desulfurized gypsum (5%wt) is added to the sieved cement clinker (95%wt) and mixed together to obtain a finished cement product.

7. The method for preparing a medium-low temperature refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement according to claim 1, characterized in that: In the step S5, desulfurized gypsum (10%wt) is added to the sieved cement clinker (90%wt), and the mixture is mixed together to obtain a finished cement product.

8. A refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement, characterized in that: The finished cement product is prepared according to any one of the medium- and low-temperature preparation methods for refined steel slag-titanium gypsum-based low-carbon sulphoaluminate cement described in claims 1-7.

Citation Information

Patent Citations

  • Method and system for producing low-alkalinity novel-mineral-system sulphoaluminate cement by utilizing steel slag

    CN109987866A

  • Method and system for producing low-alkalinity, new mineral system sulfoaluminate cement using steel slag

    CN109987866B

  • Sulphoaluminate cement clinker and cement for titanium gypsum resource utilization, and preparation method of sulphoaluminate cement clinker

    CN110372233A

  • A method for preparing sulfoaluminate cement clinker and cement for the resource utilization of titanium gypsum.

    CN110372233B

Cited By

  • Method for preparing high-sulfur iron aluminate cement by using steel slag iron extraction tailings

    CN122010431A